The Existence of Transformational Leadership Dimensions in Serat Wedhatama - Suyitno Suyitno; Teguh Supriyanto; Agus Nuryatin; Hari Bakti Mardikantoro (Universitas Negeri Semarang, 2021)
Serat Wedhatama is a literary work of the XVIII century which is said to contain work values, life values, and leadership teachings. Meanwhile, in this era of rapid change, transformational leadership is needed. This is the background of this research. This study aims to describe the dimensions of transformational leadership in Serat Wedhatama. The issue raised is how the existence of the transformational leadership dimension in Serat Wedhatama is. The method used in this research is descriptive method of documentary analysis. The data analysis technique was carried out by content analysis, which was to compare the leadership dimensions of the transformational perspective of Bass and Avolio with the substance of the leadership values ​​in Serat Wedhatama. Through an in-depth study, it was found that in Serat Wedhatama found 263 dimensions of transformational leadership, consisting of 65 (25%) dimensions of idealization of influence, 96 (37%) dimensions of inspirational motivation, 52 (20%) dimensions of intellectual stimulation, and 50 (19%) ) dimension of personal considerations. Based on these findings, it was concluded that the dimensions of transformational leadership were found in Serat Wedhatama. Thus, the leadership teachings of Serat Wedhatama are still relevant and can be empowered to prepare leaders who are in accordance with the demands of a rapidly changing era.